PEMANFATAAN SAMPAH RUMAH TANGGA MELALUI KONSEP EKONOMI SIRKULAR DI DESA TAMBAK BARU ILIR MARTAPURA - Lola Malihah; Husna Karimah; Mukhlis Kaspul Anwar; Siti Nur Sa'da Hayati; Mera Nurliana (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2023)
Community service is one of the obligations of the Tri Dharma of Tinggai University. This activity was carried out to introduce the public to the concept of a circular economy. The concept of a circular economy is considered one of the solutions to help overcome the impacts of climate change and environmental improvement efforts to support sustainable development. The concept of a circular economy can be applied through the use of household waste. Waste, which every year increases in number if not managed properly and correctly, will certainly have an impact on the environment. The target of this activity is housewives in Tambak Baru Ilir Martapura Village. The material presented was assembled with the deep conditions and damage of this ssat arch and continued with the concept of a circular economy. This activity aims to provide knowledge and understanding to the community about environmental conditions that are increasingly damaged and polluted. After this activity, it is hoped that the community will be able to implement a circular economy in their daily lives, starting from the simplest thing, namely managing household waste.